SCAN RADIO FREKWENSI (RF) DRIVE TEST DALAM TELEKOMUNIKASI - Sinaga, Dimpo (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2018)
In order to explore the potential candidates for employment, then in the world of school or college need to conduct scouting systematically between education obtained from any school or college with the business world. This can be realized through practical work so that students will be directed to achieve a professional competence. Planning is to get the optimal use of resources and maximum revenue potential while maintaining the level of quality of the system. In addition to cost considerations and spectrum allocation should also be considered. A system must be well planned so that when traffic increases, the capacity can be increased. Because the environment in each region is different, so different each macrocell and microcell network. Therefore, accurate planning is essential to ensure that the system can be enhanced capacity and improved network quality. RF planning has an important role in the design of mobile. With proper growth plan, we can reduce a lot of the problems that may arise and also reduce the cost optimization. However, if planning is bad then it will appear a lot of problems on the network and also increase the cost optimization.